PENGARUH KOMUNIKASI SBAR TERHADAP PERAWATAN KOLABORATIF ANTARPROFESI DAN DAMPAKNYA PADA KESEMBUHAN PASIEN: LITERATURE REVIEW - Metilda Mathal; Unike Natasya Luis; Nidzar Erniansyah; Sheila Nurul Anisa; Diva Febriany Syakira; Rani Hardianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study explores the impact of SBAR communication on interprofessional collaboration in healthcare. The main issue is the lack of structured communication among healthcare professionals. This lack of communication often leads to clinical errors. These clinical errors can interfere with the effectiveness of team coordination. A systematic literature review method was used to collect articles from PubMed, Google Scholar. The articles were selected based on inclusion criteria for the period 2020 to 2025. The main results show the implementation of SBAR. The application of SBAR improves clarity in information transfer. SBAR also strengthens cooperation between doctors and nurses. This cooperation contributes to reducing the risk of incidents in patients through good team coordination. These findings highlight the importance of SBAR in simplifying the exchange of important information. SBAR helps create a culture of safety for patients. This culture of safety serves to support the maximum healing process. The recommendations provided emphasize the importance of continuous training. This training aims to overcome various obstacles in its implementation in the field.